2006
DOI: 10.1101/gr.4871006
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and analysis of 10,967 full-length cDNA clones fromXenopus laevisandXenopus tropicalisreveals post-tetraploidization transcriptome remodeling

Abstract: Sequencing of full-insert clones from full-length cDNA libraries from both Xenopus laevis and Xenopus tropicalis has been ongoing as part of the Xenopus Gene Collection Initiative. Here we present 10,967 full ORF verified cDNA clones (8049 from X. laevis and 2918 from X. tropicalis) as a community resource. Because the genome of X. laevis, but not X. tropicalis, has undergone allotetraploidization, comparison of coding sequences from these two clawed (pipid) frogs provides a unique angle for exploring the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 34 publications
10
66
1
Order By: Relevance
“…Moreover, these two genes display different expression patterns during development which suggests that these two sequences have been retained in X. laevis due to spatial subfunctionalization. Studies based on full length cDNA clone analysis have demonstrated that approximately 14% of paralogous pairs in X. laevis show differential expression patterns indicative of sub-functionalization (Morin et al, 2006). Recently, we demonstrated by in situ hybridisation that this was indeed the case for the 2 pseudo-alleles coding for Annexin 4 (Massé et al, 2007).…”
Section: Two Enpp2 Genes In Xenopus Laevismentioning
confidence: 93%
“…Moreover, these two genes display different expression patterns during development which suggests that these two sequences have been retained in X. laevis due to spatial subfunctionalization. Studies based on full length cDNA clone analysis have demonstrated that approximately 14% of paralogous pairs in X. laevis show differential expression patterns indicative of sub-functionalization (Morin et al, 2006). Recently, we demonstrated by in situ hybridisation that this was indeed the case for the 2 pseudo-alleles coding for Annexin 4 (Massé et al, 2007).…”
Section: Two Enpp2 Genes In Xenopus Laevismentioning
confidence: 93%
“…Whole-genome duplications (WGDs) are widespread among eukaryotic lineages and have been identified in the ancestry of many model systems, including Saccharomyces cerevisiae (Wolfe and Shields 1997), Xenopus laevis (Morin et al 2006), Danio rerio (Postlethwait et al 2000), and Arabidopsis thaliana (Simillion et al 2002). There is increasing support for the hypothesis that two WGDs preceded the radiation of the vertebrate lineage (Panopoulou and Poustka 2005;Hughes and Liberles 2008;Putnam et al 2008;Decatur et al 2013), and nearly all land-plant genomes appear to have experienced at least one WGD, with a proposed WGD in the ancestor of all seed plants and another in the ancestor of all angiosperms (Jiao et al 2011;Amborella Genome Project 2013).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Open shrub habitat and river crossings facilitate migration between populations, while elevation differences decrease gene flow Johansson et al (2005) Common frog (Rana temporaria) 7 microsats Agricultural fragmentation has markedly different impacts on the species in different parts of its range Funk et al (2005) Columbia spotted frog (R. luteiventris) 6 microsats There is a high degree of gene flow among low-elevation populations, and elevation changes serve as barriers to gene flow have recently been sequenced and assembled, including members of three salamander families [Hynobius chinensis (Che et al 2014), A. mexicanum , Notophthalmus viridescens (Looso et al 2013)] and three anuran families [X. tropicalis (Hellsten et al 2010;Tan et al 2013), X. laevis (Morin et al 2006), Pseudacris regilla/Rana (Lithobates) clamitans (Robertson & Cornman 2014), Rana chensinensis/Rana kukunoris (Yang et al 2012), Rana muscosa/Rana sierrae (Rosenblum et al 2012), Odorrana margaretae (Qiao et al 2013), Espadarana prosoblepon/Rana (Lithobates) yavapaiensis (Savage et al 2014)]. Several of these taxa are endangered in the wild, and the availability of these transcriptome resources will allow researchers to design target-capture arrays using DNA sequence data for a large variety of amphibian species.…”
Section: Microsatsmentioning
confidence: 99%